Beam duct transition and method of manufacturing the same, particle accelerator

CN122421167BActive Publication Date: 2026-10-27INST OF MODERN PHYSICS CHINESE ACADEMY OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610841250.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-11
Publication Date
2026-10-27
Estimated Expiration
2046-06-11

AI Technical Summary

Technical Problem

[0004]本发明提供一种束流管道过渡结构及其制造方法、粒子加速器,用以解决现有加速器真空管道在变径处存在的宽频阻抗和真空度恶化的问题,同步实现了束流阻抗匹配与原位低温抽气两大核心功能,替代了传统技术中锥管过渡和远端大抽速泵的分离式方案,使加速器真空管道的设计更为高效

Benefits of technology

[0015]根据本发明提供的束流管道过渡结构的制造方法,所述去应力退火的温度为850℃。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122421167B_ABST
    Figure CN122421167B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of particle accelerators, and provides a beam pipe transition structure, a manufacturing method thereof and a particle accelerator, the beam pipe transition structure comprising a pipe body and a hollow annular wire body, the hollow annular wire body being arranged inside the pipe body, and a geometric axis of the hollow annular wire body coinciding with a central axis of the pipe body; the hollow annular wire body is integrally formed by selective laser melting 3D printing of a titanium-zirconium-vanadium-copper alloy system, an inner side surface of the hollow annular wire body forms a continuous smooth transition curved surface for the beam to pass through, an outer side surface of the hollow annular wire body forms a rough structure for increasing an effective pumping area, and a cooling flow channel extending along a circumferential direction of the hollow annular wire body is arranged inside the hollow annular wire body, and the cooling flow channel is used for passing in a low-temperature working medium. The present application can synchronously realize two core functions of beam impedance matching and in-situ low-temperature pumping, replaces a separation type scheme of a conical pipe transition and a far-end high-speed pump in a traditional technology, and makes the design of an accelerator vacuum pipe more efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of particle accelerator technology, and in particular to a beam channel transition structure and its manufacturing method, and a particle accelerator. Background Technology

[0002] In particle accelerators, the beam propagates within ultra-high vacuum tubes. When the shape or size of the tube cross-section changes—for example, in locations such as the magnetic component vacuum chamber, welded bellows, vacuum valves, or beam diagnostic equipment interfaces—discontinuities arise in the tube wall's geometric profile. From the perspective of electromagnetic field theory, the mirror current and wake field excited by the beam within the tube undergo path distortion and mode switching due to these geometric abrupt changes, thereby exciting electromagnetic field oscillations covering an extremely wide spectrum, resulting in what is known as broadband impedance. The existence of broadband impedance triggers a series of serious problems, including increased beam energy loss, exacerbated beam collective instability, increased emittance, and even overall beam quality degradation, ultimately affecting accelerator performance and the brightness of the experimental terminal.

[0003] To address the aforementioned impedance issues, existing technologies typically employ a smooth transition tapered tube as a variable-diameter connector. By gradually extending the cross-sectional change along the axial direction, the electromagnetic boundary experienced by the beam becomes progressively altered, thus suppressing broadband impedance excitation to some extent. However, this approach presents an inherent technical contradiction: the introduction of the transition tapered tube increases the inner surface area of ​​the vacuum chamber, i.e., adds additional venting area; simultaneously, the tapered tube reduces the total conductance of this section of the pipe. The increased venting area and reduced conductance lead to a significant increase in the effective gas load of the vacuum system, resulting in a deterioration of the local and even overall vacuum level. Since vacuum level is directly related to beam lifetime, a superior vacuum level is a prerequisite for ensuring a good beam lifetime. Summary of the Invention

[0004] This invention provides a beam pipe transition structure and its manufacturing method, as well as a particle accelerator, to solve the problems of wideband impedance and vacuum degradation at the diameter change point of existing accelerator vacuum pipes. It simultaneously realizes the two core functions of beam impedance matching and in-situ cryogenic pumping, replacing the traditional separate scheme of tapered tube transition and remote high-speed pump, making the design of accelerator vacuum pipes more efficient.

[0005] A first aspect of the present invention provides a beam channel transition structure, comprising: The pipe body is used for installation at joints or transition areas where the cross-sectional shape or size of the pipe changes; A hollow annular filament is disposed inside the pipe body, and the geometric axis of the hollow annular filament coincides with the central axis of the pipe body. The hollow annular filament is integrally formed by selective laser melting 3D printing of a titanium-zirconium-vanadium-copper alloy system. The inner surface of the hollow annular filament forms a continuous smooth transition surface for the beam to pass through, and the outer surface of the hollow annular filament forms a rough structure to increase the effective pumping area. The interior of the hollow annular filament is provided with a cooling channel extending circumferentially, which is used to introduce a low-temperature working fluid.

[0006] According to the beam channel transition structure provided by the present invention, the atomic percentages of each component in the titanium-zirconium-vanadium-copper alloy system are: Ti: 25-35%, Zr: 25-35%, V: 20-30%, Cu: 10-20%.

[0007] According to the beam channel transition structure provided by the present invention, the hollow annular filament has a first annular filament segment and a second annular filament segment connected to each other, and the first annular filament segment and the second annular filament segment have different contour shapes. The first annular filament segment has a first confluence ring along the circumferential direction at one end opposite to the second annular filament segment, and the second annular filament segment has a second confluence ring along the circumferential direction at one end opposite to the first annular filament segment. Both the first confluence ring and the second confluence ring are connected to the cooling channel.

[0008] According to the current conduit transition structure provided by the present invention, an inflow conduit is provided on either the first conduit ring or the second conduit ring, and an outflow conduit is provided on the other of the first conduit ring and the second conduit ring. Both the inflow pipe and the outflow pipe pass through the pipe body and extend to the outside of the pipe body.

[0009] According to the beam pipe transition structure provided by the present invention, both the first busbar and the second busbar are provided with support members, and the hollow annular filament is installed on the pipe body through the support members.

[0010] According to the beam channel transition structure provided by the present invention, the rough structure is a scale-like or granular protrusion with a surface roughness Ra between 3.2 μm and 12.5 μm.

[0011] The beam pipe transition structure provided by this invention features a hollow annular filament integrally formed from a titanium-zirconium-vanadium-copper alloy system using selective laser melting 3D printing technology within the pipe body. The inner surface of the hollow annular filament forms a continuous, smooth transition surface for beam passage, while the outer surface forms a rough structure to increase the effective pumping area. A cooling channel extending circumferentially within the hollow annular filament is used to introduce cryogenic working fluid. This simultaneously achieves two core functions: beam impedance matching and in-situ cryogenic pumping, replacing the traditional separate approach of a conical tube transition and a high-speed pump at the far end, making the design of accelerator vacuum pipes more efficient.

[0012] Specifically, through a geometrically gradual transition, broadband impedance is suppressed at its source, improving beam stability and quality, and overcoming the limitation that smooth tapered tubes can only improve geometric dimensions and cannot cope with complex three-dimensional shape abrupt changes. Utilizing the synergistic effect of low temperature (cryogenic temperature range) and a high specific surface area micro-roughness structure, an in-situ pump with extremely high pumping speed is created along the beam transmission path, effectively solving the problem of vacuum degradation caused by numerous components and complex material outgassing rates in the transition region, and improving beam lifetime.

[0013] A second aspect of the present invention provides a method for manufacturing a beam channel transition structure based on any one of the preceding claims, comprising the following steps: Selective laser melting additive manufacturing technology is used to integrally print titanium-zirconium-vanadium-copper pre-alloy powder into a hollow annular filament. The inner surface of the hollow annular filament forms a continuous smooth transition surface for the beam to pass through, and the outer surface of the hollow annular filament forms a rough structure to increase the effective pumping area. The interior of the hollow annular filament is provided with cooling channels extending along its own circumference. The hollow annular filament after printing is subjected to stress-relief annealing and surface cleaning treatment; The hollow annular filament is fixed to a predetermined position inside the accelerator vacuum pipe by welding, so that it corresponds to the diameter change or connection point of the pipe; and the cooling channel is connected to the external cooling circuit.

[0014] According to the manufacturing method of the beam channel transition structure provided by the present invention, the process parameters of the selective laser melting are set as follows: powder particle size 15-53μm, laser power 200W, scanning speed 800mm / s, and layer thickness 30μm.

[0015] According to the manufacturing method of the beam channel transition structure provided by the present invention, the stress-relief annealing temperature is 850°C.

[0016] The manufacturing method of the beam channel transition structure provided by the present invention uses SLM technology to enable the one-time molding of components with complex internal cooling channels, external micro-rough structure and internal smooth curved surface, eliminating the risk of weld leakage and additional impedance sources caused by traditional welding, machining and other manufacturing processes.

[0017] A third aspect of the present invention provides a particle accelerator including a beam pipe transition structure manufactured by any of the preceding manufacturing methods, the beam pipe transition structure being disposed inside the accelerator vacuum pipe, corresponding to a diameter change or connection point where the inner diameter of the pipe changes.

[0018] The particle accelerator provided by the present invention, having included the aforementioned beam channel transition structure, possesses all the advantages of the aforementioned beam channel transition structure. Attached Figure Description

[0019] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0020] Figure 1 This is a perspective view of the beam channel transition structure provided by the present invention.

[0021] Figure 2 This is a three-dimensional view of the hollow annular filament in the beam channel transition structure provided by the present invention.

[0022] Figure 3 This is a top view of the beam channel transition structure provided by the present invention.

[0023] Figure 4 This is a cross-sectional view of the beam channel transition structure provided by the present invention.

[0024] Figure 5 This is a flowchart of the manufacturing method of the beam channel transition structure provided by the present invention.

[0025] Figure label: 100. Beam duct transition structure; 200. Raceway-shaped cross-section duct; 300. Circular cross-section duct; 10. Pipe body; 20. Hollow annular filament; 21. First annular filament segment; 22. Second annular filament segment; 30. First busbar ring; 40. Second busbar ring; 50. Inflow pipe; 60. Outflow pipe; 70. Support component. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0027] See Figure 1 , Figure 2 , Figure 3 and Figure 4 This invention provides a beam pipe transition structure 100, which utilizes selective laser melting (SLM) 3D printing technology to fabricate a hollow annular filament 20 from a titanium-zirconium-vanadium-copper (TiZrVCu) alloy of a specific composition. This filament serves both beam impedance matching and in-situ cryogenic pumping functions, addressing the problems of broadband impedance and vacuum degradation at diameter changes in existing accelerator vacuum pipes. The beam pipe transition structure 100 includes a pipe body 10 and a hollow annular filament 20.

[0028] The pipe body 10 refers to the base structure that constitutes the accelerator vacuum pipe. The pipe body 10 is located at the connection or transition region where the cross-sectional shape or size of the pipe changes. For example, at the transition point from the racetrack-shaped cross-section pipe 200 to the circular cross-section pipe 300 in the accelerator vacuum pipe, there is a sudden change in cross-sectional shape and size. This sudden change in pipe diameter is the root cause of broadband impedance.

[0029] The hollow annular filament 20 is the core functional component of this invention, and its form is a hollow frame structure in the shape of a ring or a cage. The hollow annular filament 20 is disposed inside the pipe body 10, and its geometric axis coincides with the central axis of the pipe body 10 to ensure that its inner surface remains coaxial with the theoretical trajectory of the beam, minimizing interference with the beam. The hollow annular filament 20 is integrally formed from a titanium-zirconium-vanadium-copper (TiZrVCu) alloy system using selective laser melting (SLM) 3D printing technology. This allows components with complex internal flow channels and irregular external curved surfaces to be manufactured seamlessly, fundamentally avoiding the leakage risks and additional impedance sources that may arise from traditional welding processes in ultra-high vacuum environments.

[0030] The inner surface of the hollow annular filament 20 forms a continuous, smooth transition surface through which the beam passes. This surface is a precisely designed geometric profile that smoothly connects tube walls of different cross-sectional shapes or sizes, thereby making the geometric boundary through which the beam passes gradually rather than abruptly change.

[0031] The outer surface of the hollow annular filament 20 forms a rough structure to increase the effective air extraction area. This rough structure is not a defect, but rather a scale-like or granular micro-protrusion intentionally formed at the edge of the interlayer melt channel by controlling SLM printing parameters (such as laser power and scanning speed), making its surface area much larger than that of a smooth surface.

[0032] The hollow annular filament 20 has cooling channels extending circumferentially inside. These channels are used to contain and circulate the cryogenic working fluid. The cross-section of the channels can be circular or elliptical, and their dimensions are designed in conjunction with the filament wall thickness to achieve a balance between structural strength and cooling efficiency. For example, the wall thickness of the cooling channels in the hollow annular filament 20 is 0.5mm-2mm, and the total diameter of all cooling channels is 30%-60% of the outer diameter of the hollow annular filament 20. By adjusting the diameter and wall thickness of the cooling channels, cooling efficiency can be maximized while ensuring mechanical strength.

[0033] In accelerator physics, the geometry of the beam pipe's inner wall constitutes the electromagnetic boundary of the beam. When the pipe cross-section undergoes abrupt changes, the electromagnetic field modes at that location are drastically disturbed, resulting in a wide-spectrum impedance. The hollow annular filament 20 of this invention has its inner surface designed as a continuous, smooth Bézier or spline surface connecting different pipe shapes, minimizing the rate of change of the electromagnetic boundary. According to electromagnetic theory, a smoothly transitioning boundary condition can significantly suppress the excitation of higher-order modes, thereby eliminating the generation of broadband impedance at its source.

[0034] According to gas dynamics theory, in ultra-high vacuum under molecular flow conditions, the effective pumping speed of the pumping surface is directly proportional to its true specific surface area. Polished surfaces obtained through conventional machining have extremely limited specific surface area gain. This invention utilizes SLM technology, setting a lower laser energy density to ensure incomplete melting of the powder at the edges of each melt channel, thereby growing micron-sized scale-like or granular protrusions on a macroscopic curved surface. This micro-roughened structure increases the effective specific surface area compared to a smooth surface, improving the probability of gas molecule capture at low temperatures.

[0035] Titanium-zirconium-vanadium-copper (TiZrVCu) alloys are non-evaporative getter materials with strong chemical adsorption capabilities for reactive gases such as N2, H2O, H2, CO, and CO2. Their operating temperature is typically room temperature or even higher. The innovation of this invention lies in cooling the TiZrVCu alloy to a cryogenic temperature range (such as liquid nitrogen at 77K or liquid helium at 4.2K).

[0036] Traditional non-evaporable getter materials generally have poor thermal conductivity, making overall deep cooling difficult. This invention solves multiple problems by introducing 10-20% copper (Cu) into the alloy system: the copper-enriched phase provides a high thermal conductivity pathway in the alloy matrix, allowing the low-temperature working fluid in the internal channels to rapidly cool the entire filament to the target cryogenic temperature; simultaneously, copper lowers the alloy's melting point, making it more suitable for SLM printing processes; and it is also an excellent electrical conductor, contributing to impedance reduction.

[0037] In the liquid helium temperature range, the TiZrVCu alloy undergoes enhanced physical adsorption on its surface. Inert gases and weakly adsorbed gases that cannot be effectively captured at room temperature are firmly frozen on the surface, thus forming an in-situ cryogenic pump with extremely high pumping speed in the variable diameter region.

[0038] Based on the above structural description, the working process of the beam channel transition structure 100 is explained below: First, the hollow annular wire 20 is welded or fixed to the diameter change of the pipe body 10 by the support member 70 described below, and its internal cooling channel is connected to the external cryogenic working fluid source (such as liquid helium Dewar) and return source to form a complete sealed cooling circuit.

[0039] Then, a cryogenic working fluid (such as liquid helium) is introduced into the cooling channel. Due to the high thermal conductivity provided by copper, the entire hollow annular filament 20 is rapidly cooled to the liquid helium temperature range (approximately 4.2 K). At this point, the micro-roughened structure on the outer surface of the hollow annular filament 20 begins to strongly adsorb residual gas molecules in the vacuum cavity at low temperatures, especially gases such as H2O, H2, and CO, which are most critical to beam lifetime. This process is equivalent to placing a distributed, ultra-high pumping speed condenser pump and getter pump complex adjacent to the beam along the beam's path.

[0040] When the high-energy particle beam passes through the transition structure 100 of the beam pipe along the central axis of the pipe, the beam first encounters a continuous and smooth transition surface formed by the inner surface of the hollow annular filament 20. The electromagnetic boundary it experiences is gradually changed, thus hardly exciting any new electromagnetic field modes and suppressing the broadband impedance caused by the abrupt change in pipe diameter to an extremely low level. The beam can then pass through this connecting section smoothly and without oscillation.

[0041] As the beam continuously passes through, the cryogenic working fluid circulates continuously, carrying away the ohmic heat of the mirror current generated by the beam acting on the tube wall, as well as the adsorption heat released when adsorbing gases, ensuring that the alloy matrix is ​​always maintained at the optimal cryogenic operating point. Thus, this structure achieves impedance matching while continuously maintaining the ultra-high vacuum level in the variable diameter region.

[0042] It is understood that the beam pipe transition structure 100 provided by this invention, through the internal arrangement of a hollow annular filament 20 integrally formed by selective laser melting 3D printing technology using a titanium-zirconium-vanadium-copper alloy system, is provided within the pipe body 10. The inner surface of the hollow annular filament 20 forms a continuous smooth transition surface for the beam to pass through, while the outer surface of the hollow annular filament 20 forms a rough structure to increase the effective pumping area. A cooling channel extending circumferentially is provided inside the hollow annular filament 20 for introducing cryogenic working fluid. This simultaneously achieves the two core functions of beam impedance matching and in-situ cryogenic pumping, replacing the separate approach of the conical tube transition and the remote high-speed pump in traditional technology, making the design of the accelerator vacuum pipe more efficient.

[0043] Specifically, through a geometrically gradual transition, broadband impedance is suppressed at its source, improving beam stability and quality, and overcoming the limitation that smooth tapered tubes can only improve geometric dimensions and cannot cope with complex three-dimensional shape abrupt changes. Utilizing the synergistic effect of low temperature (cryogenic temperature range) and a high specific surface area micro-roughness structure, an in-situ pump with extremely high pumping speed is created along the beam transmission path, effectively solving the problem of vacuum degradation caused by numerous components and complex material outgassing rates in the transition region, and improving beam lifetime.

[0044] By using SLM additive manufacturing technology, the manufacturing challenges of forming complex flow channel cavities, gradient geometric surfaces, and micro-rough surfaces are solved in the same process. This achieves a seamless integrated topology with better overall structural integrity, eliminates the risk of air leakage and additional impedance sources caused by welding, and improves production efficiency and design freedom.

[0045] Furthermore, in the titanium-zirconium-vanadium-copper alloy system, the atomic percentages of each component are: Ti: 25-35%, Zr: 25-35%, V: 20-30%, Cu: 10-20%.

[0046] In other words, the alloy system is a quaternary alloy, with each component expressed as an atomic percentage (at.%): Titanium (Ti): 25-35%; Zirconium (Zr): 25-35%; Vanadium (V): 20-30%; Copper (Cu): 10-20%. The preferred ratio is Ti:Zr:V:Cu = 30%:30%:25%:15%.

[0047] Ti, Zr, and V together form the basis of the alloy's getter function. Ti, Zr, and V are non-evaporative getter materials, and their electronic structure gives them a strong chemical affinity for reactive gas molecules (such as H2, N2, H2O, CO, and CO2). Under low-temperature conditions, this chemical adsorption potential synergistically enhances with physical adsorption, resulting in getter capacity and pumping speed far exceeding those of frozen surfaces with pure physical adsorption. The proportions of the three elements are designed to be roughly balanced, aiming to form a multi-metallic compound phase, avoiding the limitations of single-phase structures, and enabling getter reactions to occur simultaneously on multiple crystal planes and at multiple adsorption sites.

[0048] The introduction of copper (10-20%) solves the problems of poor thermal conductivity, poor adaptability to printing processes, and weak impedance contribution of traditional non-evaporable getter materials.

[0049] Traditional TiZrV alloys have very low thermal conductivity, making them difficult to cool rapidly and deeply as a whole. Copper forms a highly thermally conductive pathway within the alloy matrix, allowing the entire filament to be rapidly cooled to the target temperature via the low-temperature working fluid in the internal channels. Copper's melting point (approximately 1085°C) is lower than that of Ti (approximately 1668°C), Zr (approximately 1855°C), and V (approximately 1910°C). The addition of an appropriate amount of copper lowers the overall melting point of the alloy, making it more suitable for the melt spreading and layer-by-layer bonding during selective laser melting. Furthermore, copper is an excellent conductor, helping to reduce ohmic losses when the beam mirror current flows across the filament surface, synergizing with impedance matching.

[0050] If the Cu content is below 10%, the improvement in thermal conductivity and printing processability is not significant; if the Cu content is above 20%, it may dilute the overall gas intake capacity of the NEG component and weaken the low-temperature gas extraction effect. Therefore, a Cu ratio of 10-20% achieves the optimal balance of various properties.

[0051] Therefore, the introduction of Cu improves the thermal conductivity of the alloy, solving the problem that traditional getter materials are difficult to cool deeply due to poor thermal conductivity, thus ensuring the effective realization of low-temperature getter functionality. Simultaneously, it lowers the alloy's melting point, improving the fluidity and wettability of the molten pool, enabling the high-quality printing of complex filaments with fine internal channels and surface microstructures.

[0052] See Figure 2 In some embodiments of the present invention, the hollow annular filament 20 has a first annular filament segment 21 and a second annular filament segment 22 connected to each other, the first annular filament segment 21 and the second annular filament segment 22 have different outline shapes; the first annular filament segment 21 is provided with a first confluence ring 30 in the circumferential direction at one end away from the second annular filament segment 22, and the second annular filament segment 22 is provided with a second confluence ring 40 in the circumferential direction at one end away from the first annular filament segment 21, and both the first confluence ring 30 and the second confluence ring 40 are connected to the cooling channel.

[0053] In other words, the hollow annular filament 20 is not a single uniform annular component, but rather consists of at least two filament segments, namely a first annular filament segment 21 and a second annular filament segment 22, connected axially to each other. These two filament segments have different profiles. For example, the first annular filament segment 21 can be designed as a racetrack-shaped ring to match the inner wall of a racetrack-shaped pipe, and the second annular filament segment 22 can be designed as a circular ring to match the inner wall of a circular pipe, with the two connected by a smooth transition region.

[0054] The first busbar ring 30 is disposed at the end of the first annular filament segment 21 opposite to the second annular filament segment 22 (i.e., the axial distal end of the filament segment), and extends along the entire circumference of that end. The second busbar ring 40 is disposed at the end of the second annular filament segment 22 opposite to the first annular filament segment 21, and also extends circumferentially. Both the first busbar ring 30 and the second busbar ring 40 are connected to the cooling channels inside the hollow annular filament body 20.

[0055] Because accelerator vacuum tubes often change diameter by transitioning from one cross-sectional or profile shape to another—for example, from a racetrack-shaped cross-section to a circular cross-section, with the inner dimensions abruptly changing from a 220mm × 100mm racetrack-shaped cross-section to a circular cross-section with an inner diameter of 200mm—the connected probe vacuum chamber has a 250mm circular inner diameter and ten circular holes of different sizes for installing beam diagnostic elements and monitoring equipment. These holes have diameters of 40mm, 100mm, 150mm, and 200mm, further increasing impedance discontinuities and severely impacting beam quality. If the hollow annular filament 20 uses a single uniform cross-section, it cannot perfectly fit the tube walls of different shapes at both ends simultaneously, resulting in a good fit at one end and gaps or geometric protrusions at the other, introducing new impedance sources. This embodiment of the invention resolves this contradiction by using shapes at both ends of the hollow annular filament 20 that fit the corresponding tube section cross-sections.

[0056] Each manifold ring acts like a fluid manifold: the cryogenic working fluid first enters one manifold ring, fills it, and is evenly distributed circumferentially into all the internal channels of the connected filaments; after absorbing heat as the working fluid flows through the entire annular filament, it gathers in the manifold ring at the other end and is then discharged, ensuring that each part of the multi-segment structure receives sufficient cooling flow and avoiding differences in intake performance caused by uneven local cooling. As a shared cavity, the manifold ring structure ensures uniform cooling flow along all flow paths on the circumference of the pipe, avoiding flow deviation and local hot spots caused by varying channel lengths, and ensuring consistent intake performance throughout the entire circumferential direction.

[0057] In some embodiments of the present invention, an inflow pipe 50 is provided on either the first busbar 30 or the second busbar 40, and an outflow pipe 60 is provided on the other of the first busbar 30 and the second busbar 40; both the inflow pipe 50 and the outflow pipe 60 pass through the pipe body 10 and extend to the outside of the pipe body 10.

[0058] An external cryogenic working fluid (such as liquid helium) enters a manifold (serving as a distribution chamber) through an inflow pipe 50 penetrating the wall of the pipe body 10, where it is evenly distributed circumferentially to the internal flow channels of each filament segment. After the working fluid completes its cooling function by flowing through the entire hollow annular filament 20, it merges into another manifold (serving as a collection chamber) and is finally discharged to the external return system through an outflow pipe 60 penetrating the pipe wall. This eliminates the need for complex axial routing of the working fluid pipeline inside the pipe, preventing the pipeline itself from becoming a new source of impedance, and all process interfaces are located on the outside of the pipe for easy inspection and maintenance.

[0059] The inlet and outlet of the cryogenic working fluid are located on the outside of the pipe body 10, avoiding the impact of complex internal wiring on the beam vacuum environment, and facilitating docking and connection with the external cooling system. The manifold function of the manifold is fully utilized, reducing the number of separately installed pipe interfaces and making the overall structure more compact.

[0060] In some embodiments of the present invention, both the first manifold 30 and the second manifold 40 are provided with support members 70. The support members 70 are disposed on the outer periphery (or end face) of the first manifold 30 and the second manifold 40, and are mechanical structures connecting the filament to the inner wall of the pipe. The hollow annular filament 20 is fixedly installed on the inner wall of the pipe body 10 by these support members 70, realizing the relative positioning between the two.

[0061] Because the manifold itself has high structural rigidity and circumferential continuity, it is the part of the hollow annular filament 20 that can withstand the most loads. By placing the support 70 on the manifold, the gravity and thermal stress of the hollow annular filament 20 can be effectively transferred to the pipe body 10, while avoiding direct force on the thin wall of the fragile connecting wire segment, thus reducing the risk of structural failure due to vibration or thermal expansion and contraction during vacuum operation.

[0062] The combination of the support member 70 and the manifold ring can be pre-printed. In the pipeline, the installation can be completed simply by welding or snapping the end of the support member 70 to the pipeline body 10, which simplifies the in-cavity assembly process.

[0063] In some embodiments of the present invention, the rough structure is a scale-like or granular protrusion with a surface roughness Ra between 3.2 μm and 12.5 μm.

[0064] Among them, scaly protrusions refer to semi-open, overlapping sheet-like structures at the microscopic scale; granular protrusions refer to incompletely fused spheres or ellipsoids embedded in the substrate surface. Roughness was quantified using the profile arithmetic mean deviation Ra, with values ​​limited to the range of 3.2 μm to 12.5 μm. By optimizing the SLM printing strategy, a micro-rough structure with an average Ra of approximately 5 μm was naturally formed.

[0065] During SLM printing, the laser energy density is intentionally controlled to be slightly below the level of complete smooth melting. When the laser scans across the powder layer, the powder particles at the edge of the melt channel do not absorb enough energy to completely melt and spread, thus adhering to the sidewall of the melt channel in a semi-fused state. As layers are stacked, these semi-fused particles accumulate, forming microscopic protrusions resembling scales or granules. By adjusting parameters such as laser power, scanning speed, and powder particle size, the degree of this incomplete melting can be controlled, thereby obtaining the roughness Ra value for the target area.

[0066] In ultra-high vacuum under molecular flux conditions, the probability of gas molecules colliding with a solid surface is directly related to the actual surface area. Traditionally polished metal surfaces have extremely small microscopic undulations, and their specific surface area (the ratio of actual surface area to projected area) is typically only slightly greater than 1. This invention, through the construction of microscopic protrusion structures with Ra values ​​ranging from 3.2 μm to 12.5 μm, increases the effective specific surface area by 2 to 5 times. This means that within the same macroscopic projected area, it provides 2 to 5 times more gas molecule attachment sites than a smooth surface, thereby significantly improving gas capture efficiency and effective pumping speed under cryogenic conditions.

[0067] See Figure 5 The present invention also provides a method for manufacturing a beam channel transition structure 100 based on any of the above embodiments, comprising the following steps: Step S100: Using selective laser melting additive manufacturing technology, titanium-zirconium-vanadium-copper pre-alloy powder is integrally printed into a hollow annular filament 20. The inner surface of the hollow annular filament 20 forms a continuous smooth transition surface for the beam to pass through, and the outer surface of the hollow annular filament 20 forms a rough structure to increase the effective pumping area. The interior of the hollow annular filament 20 is provided with cooling channels extending along its circumference.

[0068] Understandably, this step employs selective laser melting (SLM) technology, using TiZrVCu pre-alloyed powder as the raw material. Through layer-by-layer powder spreading and laser scanning, a hollow annular filament 20 with three functional structural features is directly printed: a smooth inner curved surface, a rough outer structure, and internal cooling channels. These three structures are simultaneously manufactured in the same SLM process, achieving complex internal and surface topologies that are impossible to achieve with traditional subtractive or assembly processes.

[0069] Step S200: Perform stress-relieving annealing and surface cleaning on the printed hollow annular filament 20.

[0070] Understandably, this step involves stress-relief annealing and surface cleaning of the SLM-formed blank. The extremely rapid melting rate during SLM introduces residual thermal stress within the component. Stress-relief annealing aims to eliminate these stresses, stabilize the component's dimensions and mechanical properties, and prevent thermal deformation or cracking due to stress release during subsequent cooling cycles. Surface cleaning removes contaminants such as semi-fused powder and oxide scale remaining on the surface after printing, ensuring leakage rate and vacuum cleanliness.

[0071] Step S300: The hollow annular filament 20 is fixed to a predetermined position inside the accelerator vacuum pipe by welding, so that it corresponds to the diameter change or connection point of the pipe; and the cooling channel is connected to the external cooling circuit.

[0072] Understandably, in this step, the qualified hollow annular filament 20, after post-processing, is fixed to a pre-defined diameter-changing position inside the accelerator vacuum pipe by welding. Welded connections offer advantages such as low outgassing rate and high structural strength, making them suitable for ultra-high vacuum environments. Simultaneously, the cooling channels inside the hollow annular filament 20 are sealed to the external cryogenic working fluid supply and return system (i.e., the external cooling circuit).

[0073] SLM (Self-Made Manufacturing) technology enables the one-step molding of components with complex internal cooling channels, externally roughened structures, and smooth internal surfaces, eliminating the risk of weld leaks and additional impedance sources associated with traditional welding and machining processes. The smooth surfaces, roughened surfaces, and internal channels are formed simultaneously in the same process, ensuring relative positional accuracy and dimensional compatibility. From printing and post-processing to final assembly and welding, a complete clean manufacturing process is established, which helps maintain high vacuum compatibility of materials.

[0074] Furthermore, the process parameters for selective laser melting were set as follows: powder particle size 15-53μm, laser power 200W, scanning speed 800mm / s, and layer thickness 30μm.

[0075] The powder particle size ranges from 15 to 53 μm. This range balances smooth powder spreading with sufficient melting, preventing excessively fine powder from agglomerating due to van der Waals forces and excessively coarse powder from causing insufficient energy penetration. The laser power of 200 W provides sufficient energy to melt the TiZrVCu alloy powder. The scanning speed of 800 mm / s ensures high forming efficiency while guaranteeing sufficient powder melting. The layer thickness of 30 μm matches the powder particle size, ensuring good metallurgical bonding between layers.

[0076] At a laser power of 200W and a laser speed of 800mm / s, the energy density of the laser spot acting on a 15-53μm powder layer is sufficient to completely melt the alloy powder and form a metallurgical bond with the underlying matrix. This results in a dense, non-porous matrix structure for the filament, enabling it to withstand low-temperature working fluid pressure without leakage.

[0077] This energy density is not extremely high; at the boundary of the melt channel edge, the energy is slightly lower than at the center. Simultaneously, the higher melting threshold of larger particle size powder (close to 53 μm) may be superimposed, thus naturally generating a semi-fused morphology at the melt channel edge within the set layer thickness. A row of tiny, discontinuous protrusions left at the edge of each scanning path, after layer-by-layer accumulation, forms a micro-rough structure of the target magnitude (Ra 3.2-12.5 μm).

[0078] The TiZrVCu alloy has a relatively low melting point and good fluidity due to its copper content. These parameters are optimized to address the changes in thermophysical properties (increased thermal conductivity and lower melting point) caused by the copper component in this alloy system, and can effectively suppress spheroidization or cracking problems commonly found in the printing of high-reflectivity metals or refractory metals.

[0079] Furthermore, the specific temperature parameters for stress-relief annealing in the post-processing step are approximately 850°C.

[0080] Because the TiZrVCu alloy undergoes an extremely high cooling rate (typically reaching 10) during the SLM forming process. 4 -10 6 (K / s), which will accumulate thermal residual stress inside the component. 850℃ is in the stress-relief annealing temperature range of this alloy system. Holding at this temperature allows metal atoms to effectively relax internal lattice distortion and macroscopic stress through diffusion, dislocation movement and recovery, so that the component can restore stable geometric dimensions and mechanical state, and prevent deformation or cracking under subsequent cooling contraction or stress conditions.

[0081] For non-evaporative getter materials, hydrogen has the strongest adsorption capacity but is also the most easily passively absorbed and stored in the air. The SLM printing process and subsequent atmospheric exposure may result in a certain amount of hydrogen in the surface layer. Under high-temperature vacuum annealing at 850℃, the solid solubility of hydrogen in the alloy decreases and the diffusion rate increases significantly, thereby allowing the absorbed hydrogen to diffuse and desorb from the matrix, ensuring the initial getter capacity before application.

[0082] This invention also provides a particle accelerator, including a beam pipe transition structure 100 manufactured by the manufacturing method provided in any of the above embodiments. The beam pipe transition structure 100 is disposed inside the accelerator vacuum pipe, corresponding to the diameter change point or connection point of the pipe inner diameter.

[0083] In particle accelerators, especially large-scale scientific research facilities such as third-generation synchrotron radiation sources or free-electron lasers, the beam channel transition structure 100 directly determines the beam quality (brightness, stability) and vacuum lifetime. Integrating the transition structure obtained using this specific manufacturing method into the particle accelerator gives the particle accelerator itself a substantial performance improvement.

[0084] Within its variable diameter region, the inclusion of a TiZrVCu hollow annular filament 20 manufactured integrally by SLM enables stable beam transmission at locations of cross-sectional area or shape changes without introducing additional venting sources or increasing beam impedance. This results in higher beam stability (a higher threshold for collective beam instability due to lower impedance), longer beam lifetime, and better, superior tube vacuum for the particle accelerator.

[0085] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A beam channel transition structure, characterized in that, include: The pipe body is used for installation at joints or transition areas where the cross-sectional shape or size of the pipe changes; A hollow annular filament is disposed inside the pipe body, and the geometric axis of the hollow annular filament coincides with the central axis of the pipe body. The hollow annular filament is integrally formed by selective laser melting 3D printing of a titanium-zirconium-vanadium-copper alloy system. The inner surface of the hollow annular filament forms a continuous smooth transition surface for the beam to pass through, and the outer surface of the hollow annular filament forms a rough structure to increase the effective pumping area. The interior of the hollow annular filament is provided with a cooling channel extending circumferentially, which is used to introduce a low-temperature working fluid.

2. The beam channel transition structure according to claim 1, characterized in that, In the titanium-zirconium-vanadium-copper alloy system, the atomic percentages of each component are: Ti: 25-35%, Zr: 25-35%, V: 20-30%, Cu: 10-20%.

3. The beam channel transition structure according to claim 1, characterized in that, The hollow annular filament has a first annular filament segment and a second annular filament segment that are connected to each other, and the first annular filament segment and the second annular filament segment have different outline shapes; The first annular filament segment has a first confluence ring along the circumferential direction at one end opposite to the second annular filament segment, and the second annular filament segment has a second confluence ring along the circumferential direction at one end opposite to the first annular filament segment. Both the first confluence ring and the second confluence ring are connected to the cooling channel.

4. The beam channel transition structure according to claim 3, characterized in that, An inflow pipe is provided on either the first bus ring or the second bus ring, and an outflow pipe is provided on the other of the first bus ring and the second bus ring. Both the inflow pipe and the outflow pipe pass through the pipe body and extend to the outside of the pipe body.

5. The beam channel transition structure according to claim 3, characterized in that, Both the first and second manifolds are provided with support members, and the hollow annular filament is installed on the pipe body through the support members.

6. The beam channel transition structure according to claim 1, characterized in that, The rough structure is a scale-like or granular protrusion with a surface roughness Ra between 3.2 μm and 12.5 μm.

7. A method for manufacturing a beam channel transition structure based on any one of claims 1 to 6, characterized in that, Includes the following steps: Selective laser melting additive manufacturing technology is used to integrally print titanium-zirconium-vanadium-copper pre-alloy powder into a hollow annular filament. The inner surface of the hollow annular filament forms a continuous smooth transition surface for the beam to pass through, and the outer surface of the hollow annular filament forms a rough structure to increase the effective pumping area. The interior of the hollow annular filament is provided with cooling channels extending along its own circumference. The hollow annular filament after printing is subjected to stress-relief annealing and surface cleaning treatment; The hollow annular filament is fixed to a predetermined position inside the accelerator vacuum pipe by welding, so that it corresponds to the diameter change or connection point of the pipe; and the cooling channel is connected to the external cooling circuit.

8. The method for manufacturing the beam channel transition structure according to claim 7, characterized in that, The process parameters for selective laser melting are set as follows: powder particle size 15-53μm, laser power 200W, scanning speed 800mm / s, and layer thickness 30μm.

9. The method for manufacturing the beam channel transition structure according to claim 8, characterized in that, The stress-relief annealing temperature is 850℃.

10. A particle accelerator, characterized in that, Includes a beam pipe transition structure manufactured by the manufacturing method of any one of claims 7 to 9, the beam pipe transition structure being disposed inside the accelerator vacuum pipe, corresponding to a diameter change or connection point where the inner diameter of the pipe changes.

Citation Information

Patent Citations

  • Compact synchrotron vacuum system and design method

    CN120456402A

  • Button-type signal feed-through for beam position detector and preparation method of button-type signal feed-through

    CN121038086A